2005-06 Farm Bill Survey: Florida Producer Views on Rural Development; Open Space and Farmland Preservation; Labor; Research Funding Allocation; and Inclusion of Fruits, Vegetables, and Specialty Crops in Federal Government Commodity Programs - Rodney L. Clouser (EDIS)
FE664, a 5-page report by Rodney L. Clouser, is one of four fact sheets reporting information collected from Florida producers concerning attitudes and views regarding U.S. Congressional enactment of the next farm bill. This fact sheet focuses on five questions that were asked specifically of Florida producers and not necessarily by the other states participating in the survey. Published by the UF Department of Food and Resource Economics, October 2006.